A9.6 Effect of mPGES-1 targeting on lipid metabolism in human cells. (31st January 2014) - Idborg, Helena; Raouf, Joan; Ossipova, Elena; Checa, Antonio; Olsson, Petter; Leclerc, Patrick; Oliynik, Ganna; Wheelock, Craig; Jakobsson, Per-Johan; Korotkova, Marina
Abstract : Background: Microsomal prostaglandin E synthase-1 (mPGES-1) is the terminal enzyme in the induced PGE2 production and well-recognised target for the development of novel anti-inflammatory drugs. Genetic deletion and inhibition of mPGES-1 appears to be protective in experimental models of arthritis. Targeting mPGES-1 alters eicosanoid profiles and may potentially affect the metabolism of other lipids. Fatty acids (FA) play essential roles as energy substrates, membrane structural components, second messengers and precursors of lipid mediators. Genetic deletion of mPGES-1 resulted in reduced levels of MUFA in the spleen suggesting a decreased activity/expression of stearoyl-CoA-desaturase (SCD). SCD has been implicated in modulation of inflammation. However whether mPGES-1 inhibition affects lipid metabolism in human cells is not known. Objective: To investigate the effect of mPGES-1 deletion/inhibition on lipid metabolism in human cells. Methods : A549 cells were induced with IL-1b and treated with mPGES-1 inhibitor (compound III) or COX-2 inhibitor (NS398). Eicosanoid profiles were analysed using LC-MS/MS and protein profiles were analysed using mass spectrometry based proteomics. FA composition of total lipids was determined using gas chromatography with flame ionization detector and sphingolipids were analysed by LC-MS/MS. Results: Proteomic analysis of A549 cells identified the reduction of SCD levels in response to treatment with mPGES-1 or COX-2 inhibitors, as well as the suppression of the levels of a number of proteins involved in metabolism of fatty acids and sphingolipids. Conclusion: Data reveals that down-regulation of COX-2/mPGES-1/ PGE2 axis affects the lipid metabolism in A549 cells. These effects have important implications regarding potential consequences of pharmacologic mPGES-1 inhibition.